The morphological characters and DNA barcoding identification of sweet river prawn Macrobrachium esculentum (Thallwitz, 1891) from Rongkong watershed of South Sulawesi, Indonesia - Jurniati Jurniati; DIANA ARFIATI; SAPTO ANDRIYONO; ASUS MAIZAR SURYANTO HERTIKA; ANDI KURNIAWAN; WENDY ALEXANDER TANOD (Society for Indonesian Biodiversity, 2021)
Abstract. Jurniati, Arfiati D, Andriyono S, Hertika AMS, Kurniawan A, Tanod WA. 2021. The morphological characters and DNA Barcoding identification of sweet river prawn Macrobrachium esculentum (Thallwitz, 1891) from Rongkong watershed of South Sulawesi, Indonesia. Biodiversitas 22: 113-121. Freshwater prawns of the genus Macrobrachium Bate, 1868 (Crustacea: Palaemonidae), play an essential role in freshwater ecosystems. Apart from being a crucial biotic component, freshwater prawns are also an important fishery commodity. The sweet river prawn Macrobrachium esculentum (Thallwitz, 1891) is a freshwater prawn that inhabits the Wallacea area and is a key constituent of crustacean biodiversity. However, morphological studies on Macrobrachium prawns that inhabit Sulawesi are still minimal. This study is the first report on the morphological and DNA barcoding identification of freshwater prawn M. esculentum downstream of the Rongkong watershed in South Sulawesi, Indonesia. The morphological characterization includes morphometric and meristic characteristics and is complemented by the DNA barcoding of the cytochrome c oxidase subunit I (COI) region. The analysis of the morphometric characteristics showed the formation of two population groups: the Waelawi River group and the Salujambu-Pombakka Rivers group. However, the meristic characteristics of M. esculentum from the three rivers were not significantly different. Meanwhile, the DNA barcoding analysis confirmed that the samples collected from the three rivers belong to the same species. This study provides information on the identification of M. esculentum inhabiting the Rongkong watershed and its population characters and grouping based on morphometric and meristic characteristics. This information can contribute to the management of fishery resources and the conservation of M. esculentum prawn resources in the Rongkong watershed, South Sulawesi, Indonesia.